2015
DOI: 10.4149/bll_2015_035
|View full text |Cite
|
Sign up to set email alerts
|

Serum omentin levels predicts mesenteric ischemia

Abstract: Abstract:Background:Acute mesenteric ischemia (AMI) is an intestinal vascular disease with high mortality. Clinical diagnosis of acute mesenteric ischemia is diffi cult. Adipose tissue is an important mediator of metabolism and infl ammation.Omentin is produced by visceral adipose tissue and decreased serum levels of omentin are associated with poor metabolic outcomes. We aimed to investigate whether serum omentin level predicts early diagnosis of AMI before development of transmural ischemia. Methods: Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…6 For instance, omentin, cardiothrophin and neuregulins as adipocytokines are found to be correlated with various inflammatory, metabolic and impaired glucose tolerance conditions including mesenteric ischemia, diabetes, diabetic nephropathy, chronic kidney disease, pancreatitis and pregnancy. [7][8][9][10][11] Neuregulin 4 (NRG-4), a novel brown adipose tissue (BAT)-secreted adipokine, functions in an autocrine/paracrine or endocrine manner. 12 It has been demonstrated that NRG-4 exerts beneficial metabolic effects in mice.…”
mentioning
confidence: 99%
“…6 For instance, omentin, cardiothrophin and neuregulins as adipocytokines are found to be correlated with various inflammatory, metabolic and impaired glucose tolerance conditions including mesenteric ischemia, diabetes, diabetic nephropathy, chronic kidney disease, pancreatitis and pregnancy. [7][8][9][10][11] Neuregulin 4 (NRG-4), a novel brown adipose tissue (BAT)-secreted adipokine, functions in an autocrine/paracrine or endocrine manner. 12 It has been demonstrated that NRG-4 exerts beneficial metabolic effects in mice.…”
mentioning
confidence: 99%
“…Decreased levels of omentin in synovia have been reported in rheumatoid arthritis 6 , and reduced omentin messenger RNA expression has been reported in the omentum of subjects with Chrohn's disease 7 . Authors reported reduced omentin levels in acute appendicitis 8 and mesenteric ischemia settings 9 . On the other hand, the effects of C-reactive protein and tumor necrosis factor-alpha on endothelial cells were reduced by omentin 10 .…”
Section: Discussionmentioning
confidence: 99%
“…This serum marker turns positive in 30 min. The study concluded that, for thromboembolism of the SMA, bowel ischemia of any other cause, and patients needing a laparotomy, the sensitivity and predictive value of a negative Ddimer test were 100% [48]. Additionally, in another study, with median levels of 1.6 mg/L, patients with AMI had significantly higher levels of D-dimer than patients in the control group [47].…”
Section: D-dimermentioning
confidence: 95%